Fully Automated Classroom Attendance System - Al Hajri, Eid; Hafeez, Farrukh; N V, Ameer Azhar (International Journal of Interactive Mobile Technologies (iJIM), 2019)
This paper is based on study and implementation of the pilot project for customized, automated, highly secured class room management system known as JIC CMS (Jubail Industrial College Class room management System). In this research paper, the strategies, design, development and implementation of a pilot project for class room attendance management systems is explained in detail. As a pilot project, mobile app is built on Android platform using Xamarin programming. Prototype of proposed system provides high level of authentication by embedding face recognition and biometric verification together with RFID system. Though given model features are specially designed for our college needs, but this model can be modified for general usage and can be applied for all academic levels i.e. school, college, universities. Among the other features of system, one important feature is selection of system to work in smart mode in which system closes after predefined time and uploaded automatically to the web server.